Comparison of Intensive Care Unit and General Wards Nurses’ Emotional Reactions and Health Status - Nouroozi Kushali, ali; Hajiamini, zahra; Ebadi, abas; Khamseh, feriyal; Rafieyan, zahra; Sadeghi, azam (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Nurses in their work settings are exposed to pain,suffer and death of their patients which may affect their health status and emotional reactions . This study aimed to compare ICU and general wards’ nurses health status and emotional reactions . Method and materials. This is a descriptive- cross sectional study which was performed on 103 intensive care unit nurses and 210 nurses in general wards in two of Baqhiatalah (a.j) university hospitals in 2010. The sample of the study was selected by systematic random sampling method’. Data were collected by GHQ12 &DASS21 questionnaires to evaluate emotional reactions and general health status of nurses. Data were analyzed by SPSS15 software descriptive analytical statistics such as chi-square tests. Results: On average, 33% of nurses in the study had stress 33.9%, anxiety and 30.8% depression range of mild to very severe and showed that only was more depression in the intensive care units nursing (P <0.05).Although About 30% of nurses general health are not desirable in terms and the difference was not statistically significant in two groups of nurses studied. Conclusion: The results demonstrated that approximately ⅓ of both groups intensive care units and other wards nurses had general health are not desirable in terms and at least one of emotional reactions (stress, anxiety or depression) even was more depression in the intensive care units nursing. Given the importance of nursing due and patient care, Management measures to assess and control factors to this problem is necessary. Keywords: general health, emotional reactions, nurse, intensive care units